2015
DOI: 10.1186/s13075-015-0704-4
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency in chronic inflammatory rheumatic diseases: results of the cardiovascular in rheumatology [CARMA] study

Abstract: IntroductionThe aim was to study the association between 25-hydroxyvitamin D (25(OH)D) levels and the clinical characteristics of patients with chronic inflammatory rheumatic diseases (CIRD).MethodsWe studied a cross-section from the baseline visit of the CARMA project (CARdiovascular in rheuMAtology), a 10-year prospective study evaluating the risk of cardiovascular events in rheumatoid arthritis (RA), ankylosing spondylitis (AS) and psoriatic arthritis (PsA) patients, and non-CIRD patients who attended rheum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
22
0
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 31 publications
4
22
0
4
Order By: Relevance
“…Avoidance of sunshine, photoprotection, renal insufficiency, and the use of medications which alter the metabolism of vitamin D or downregulate the functions of the vitamin D receptor like glucocorticoids, anticonvulsants, antimalarials, and the calcineurin inhibitors are some of the causes of VDD as shown in Figure 2 [37]. In a study by Toloza, vitamin D insufficiency was found in 66 [59][60][61][62]. Levels of 25(OH)D3 were also found to be negatively correlated to CRP and ESR [62].…”
Section: Slementioning
confidence: 99%
“…Avoidance of sunshine, photoprotection, renal insufficiency, and the use of medications which alter the metabolism of vitamin D or downregulate the functions of the vitamin D receptor like glucocorticoids, anticonvulsants, antimalarials, and the calcineurin inhibitors are some of the causes of VDD as shown in Figure 2 [37]. In a study by Toloza, vitamin D insufficiency was found in 66 [59][60][61][62]. Levels of 25(OH)D3 were also found to be negatively correlated to CRP and ESR [62].…”
Section: Slementioning
confidence: 99%
“…Bu nedenle D vitamini yetersizliğin-de enfeksiyonların ve otoimmün hastalıkların görülme riski artmaktadır [8] . Kronik inflamatuvar romatizmal hastalıklar içinde özellikle romatoid artritte serum 25 hidroksi (OH) D vitamini eksikliğinin yüksek hastalık aktivitesi ile ilişkili olduğuna dair çalışmalar mevcut olmakla birlikte bu konu literatürde henüz netlik kazanmamıştır [9][10][11] . Bu çalışmanın amacı, RA hastalarında serum 25 (OH) D vitamini düzeyinin Disease Activity Score (DAS) 28 skoru ile ölçülen hastalık aktivitesi, demografik özellikler ve laboratuvar parametreleri ile ilişkisini incelemektir.…”
unclassified
“…Однако работы по изучению содержания витамина D у пациентов с ПсА немногочислены. Результаты этих исследований сви-детельствуют о более низком уровне витамина D у та-ких больных по сравнению со здоровыми лицами [22,[32][33][34]. Так, например, работа, представленная ис-панскими авторами [34], продемонстрировала одина-ковую частоту дефицита витамина D у больных РА, анкилозирующим спондилитом и ПсА (40,5; 39,7 и 40,9% соответственно), которая была достоверно выше, чем у лиц без хронических воспалительных ревматических заболевний (26,7%).…”
unclassified
“…Результаты этих исследований сви-детельствуют о более низком уровне витамина D у та-ких больных по сравнению со здоровыми лицами [22,[32][33][34]. Так, например, работа, представленная ис-панскими авторами [34], продемонстрировала одина-ковую частоту дефицита витамина D у больных РА, анкилозирующим спондилитом и ПсА (40,5; 39,7 и 40,9% соответственно), которая была достоверно выше, чем у лиц без хронических воспалительных ревматических заболевний (26,7%). Бивариантный анализ показал, что больные ПсА с дефицитом вита-мина D достоверно меньше времени проводили на солнце и реже дополнительно принимали препараты витамина D и кальция, а также чаще страдали ожире-нием [34].…”
unclassified